2018
DOI: 10.1038/s41426-018-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Saliva as a source of reagent to study human susceptibility to avian influenza H7N9 virus infection

Abstract: Avian influenza H7N9 viruses are an important public health concern due to their high mortality rate and potentials for future pandemics. We investigated human susceptibility to H7N9 viruses using recombinant H7N9 hemagglutinin (HA) proteins as a probe and found a strong association between H7N9 infections and HA binding among saliva samples from 32 patients and 60 uninfected controls in Jiangsu province, China, during the 2016 epidemic season. We also found that sialyl Lex (SLex) antigen that was recognized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…We have proved the concept by generating a chimeric S-VP8* nanoparticle that contains 60 displayed rotavirus neutralizing antigen VP8*s on the surface of the self-assembled S particles [17]. A similar principle has also been used for making S-HA1 particles that display the HA1 antigens of the H7N9 influenza virus [18].…”
Section: Introductionmentioning
confidence: 93%
“…We have proved the concept by generating a chimeric S-VP8* nanoparticle that contains 60 displayed rotavirus neutralizing antigen VP8*s on the surface of the self-assembled S particles [17]. A similar principle has also been used for making S-HA1 particles that display the HA1 antigens of the H7N9 influenza virus [18].…”
Section: Introductionmentioning
confidence: 93%
“…Saliva samples from healthy employees in the Cincinnati Children’s Hospital Medical Center collected for studies of norovirus and rotavirus binding profiles of host histo blood group antigens in our previous studies [ 17 , 18 ] were used. Recombinant H7N9 and 1918 H1N1 HAs were constructed and expressed as described previously [ 16 ]. The 95 tested saliva sample donors were sorted based on the OD binding signals of H7N9 HA (top panel).…”
Section: Introductionmentioning
confidence: 99%
“…The H1 225G subtype viruses are responsible for the severe pathogenicity and high fatality of the 1918 pandemic. We first formulated the hypothesis of polymorphic 2,3-Sias in humans after finding that only ~30% of human subjects revealed ELISA binding signals in their saliva specimens by a recombinant HA of the avian H7N9 viruses that bind 2,3-but not 2,6-linked Sias [16]. Our further studies of saliva specimens from a panel of healthy adults confirmed the results with ~24% the saliva panel binding to the H7 HA antigens but, by comparison, 100% of the saliva panel revealed binding signals with a recombinant 1918 H1 antigen that is known to recognize 2,6-Sias (Fig 1).…”
Section: Introductionmentioning
confidence: 99%
“…As the natural barrier, it has been proved that the soluble salivary proteins glycosylated with terminal α2-3/6-linked Sia can neutralize and inhibit influenza viruses in this way efficiently [22][23][24]. And the protein sialylation level in saliva has been expected to be used as an indicator to estimate the individual susceptibility to influenza virus [25].…”
Section: Introductionmentioning
confidence: 99%